Comprehensive symptom assessment using Integrated Palliative care Outcome Scale in hospitalized heart failure patients - Yasuhiro Hamatani; Moritake Iguchi; Yurika Ikeyama; Atsuko Kunugida; Megumi Ogawa; Natsushige Yasuda; Kana Fujimoto; Hidenori Ichihara; Misaki Sakai; Tae Kinoshita; Yasuyo Nakashima; Masaharu Akao (ESC Heart Failure)
Abstract Aims Patients with heart failure (HF) may have variable unrecognized symptom burdens. We sought to investigate the details, determinants, and prognostic significance of symptom burden in hospitalized patients with HF. Methods and results We prospectively evaluated consecutive hospitalized patients with HF as primary diagnosis at our institution using the Integrated Palliative care Outcome Scale (IPOS) both on admission and at discharge. The IPOS, which is a well‐validated multi‐dimensional symptom assessment scale among advanced illness, consists of 17 questions for enquiring about physical symptoms (10 items), emotional symptoms (4 items) and communication and practical issues (3 items) using a 5‐point Likert scale (0 [best]–4 [worst] points). Clinically relevant symptoms were defined as ≥2 points for each IPOS item. Worsening symptom burden was defined as the total IPOS score at discharge being poorer than that on admission. Of 294 patients (mean age: 77.5 ± 12.0 years, male: 168 patients, New York Heart Association class IV: 96 patients, mean left ventricular ejection fraction [LVEF]: 44%, and median N‐terminal pro B‐type natriuretic peptide [NT‐proBNP] level: 4418 ng/L), the median (IQR) total IPOS score on admission was 19 (12, 27) and they were widely distributed (minimum: 0 – maximum: 52). The total IPOS score on admission was not correlated with the HF severity, including LVEF (Spearman's ρ = −0.05, P = 0.43), NT‐proBNP levels (Spearman's ρ = 0.08, P = 0.20) or in‐hospital mortality prediction model (GWTG‐HF risk score) (Spearman's ρ = 0.01, P = 0.90). Total IPOS scores significantly decreased during hospitalization as a whole (median [IQR]: 13 [6, 21] at discharge; P < 0.001 vs. those on admission). All of the four emotional symptoms (patient anxiety, depression, family anxiety and feeling at peace) remained in the top 5 of clinically relevant symptoms at discharge, whereas none of 10 physical symptoms were nominated. Worsening symptom burden was noted in 28% of the patients during hospitalization, and was independently associated with higher all‐cause mortality after discharge (hazard ratio: 2.28, 95% confidence interval: 1.02–5.09; P = 0.044) even after adjustment by age and HF mortality prediction model (MAGGIC risk score). Conclusions We revealed that hospitalized patients with HF had multi‐dimensional symptom burdens which varied among individuals and were not correlated with the disease severity. Emotional symptoms, such as anxiety and depression, were the main clinically relevant symptoms at discharge. A worsening IPOS score was noted in a quarter of patients with HF and was associated with a poor prognosis, suggesting the importance of holistic symptom assessment during the course of hospitalization for HF.